Optimizing the delivery of genetic and advanced diagnostic testing in the province of Ontario: challenges and implications for laboratory technology assessment and management in decentralized healthcare systems. (31st December 2022) - Husereau, Don; Sullivan, Terrence; Feilotter, Harriet E.; Gomes, Marcio M.; Juergens, Rosalyn; Sheffield, Brandon S.; Kassam, Shaqil; Stockley, Tracy L.; Jacobs, Philip
Abstract: Aims: The Canadian province of Ontario provides full coverage for its residents (pop.14.8 M) for hospital-based diagnostic testing. Historical governance of the healthcare system and a legacy scheme of health technology assessment (HTA) and financing has led to a suboptimal approach of adopting advanced diagnostic technology (i.e. protein expression, cytogenetic, and molecular/genetic) for guiding therapeutic decisions. The aim of this research is to explore systemic barriers and provide guidance to improve patient and care provider experiences by reducing delays and inequity of access to testing, while benefitting laboratory innovators and maximizing system efficiency. Materials and methods: A mixed-methods approach including literature review, semi-structured interviews, and a multi-stakeholder forum involving patient representatives ( n = 1), laboratory leaders ( n = 6), physicians ( n = 5), Ministry personnel ( n = 4), administrators ( n = 3), extra-provincial experts, and researchers ( n = 7), as well as pharmaceutical ( n = 5) and diagnostic companies ( n = 2). The forum considered evidence of good practices in adoption, implementation, and financing laboratory services and identified barriers as well as feasible options for improving advanced diagnostic testing in Ontario. Results: Overarching challenges identified included: barriers to define what is needed; need for a clear approach to adoption; and the need for more oversight and coordination. Recommendations to address these included a shift to an anticipatory system of test adoption, creating a fit-for-purpose system of health technology management that consolidates existing evaluation processes, and modernizing the governance and financing of testing so that it is managed at a care-delivery level. Conclusions: The proposals for change in Ontario highlight the role that HTA, governance, and financing of health technology play along the continuum of a health technology life cycle within a healthcare system where decision-making is highly decentralized. Resource availability and capacity were not a concern – instead, solutions require higher levels of coordination and system integration along with innovative approaches to HTA.